The rescue - Lasky, Kathryn (New York : Scholastic, 2004)
"Even though Soren was kidnapped and taken to the St. Aegolius School for Orphaned Owls, he has longed to see his sister, Eglantine, again. Now Eglantine is back in Soren's life, but she's been through an ordeal too terrible for words. And Ezylryb, Soren's mentor, has disappeared.... In order to rescue him, Soren must embark upon a perilous quest."--[P. 4] of cover.
RL4.
008-012.
850
Accelerated Reader AR
Keywords: Owls -- Juvenile fiction; Fantasy fiction